The Future of Finance and Financial Economics - Mohammed Khayum (Global Business and Finance Review, 2009)
The last eighteen months have witnessed extraordinary financial market disruptions, a contagion of bank failures or near failures, an unprecedented loss of confidence in the global financial system, and wide-ranging strategies by governments of major economies to unlock credit markets and restore confidence in their respective banking systems. Relative unpreparedness for the disruptions triggered by the subprime mort- gage crisis originating in the Unites States in 2007 has prompted serious questioning of the focus and usefulness of academic finance and the lack of transparency in some components of the global financial system. This article provides an overview of major questions that have surfaced and the issues that are likely to be areas of focus for years to come.